Origin of hydrogen trapping site in vanadium carbide precipitation strengthening steel. (July 2018) - Takahashi, Jun; Kawakami, Kazuto; Kobayashi, Yukiko
Abstract: We successfully achieved atomic scale visualization of hydrogen atoms at trapping sites associated with the nano-sized precipitates of titanium carbide and vanadium carbide in ferritic steels using a modified three-dimensional atom probe with a deuterium charge cell. We proposed that the hydrogen trapping sites of fine carbide precipitates were at the (001) broad interface between the precipitate and the ferrite matrix. In this study, the precipitate size dependence in the trapping site and its energy was systematically investigated in vanadium carbide precipitation strengthening steels with various aging times. Hydrogen thermal desorption spectrometry analysis showed that the hydrogen trapping energy in the peak- and over-aged steels was larger than that in the under-aged steel. Atom probe tomography analysis showed the {001} platelets of vanadium carbide were covered by charged deuterium atoms in the peak-aging steel with large trapping energy, whereas no deuterium atoms around the {001} platelets were observed in the under-aged steel with small trapping energy. High-resolution transmission electron microscopy observation showed that misfit dislocations hardly appeared on the (001) surface of the precipitates in the two steels with large and small trapping energies. In contrast, the vanadium–carbon atomic ratios of vanadium carbide precipitates were definitely different between the two steels with large and small trapping energies. The precipitates in the under-aged steel with small trapping energy showed a chemical composition similar to VC, whereas the precipitates in the peak- and over-added steels with large trapping energy showed a chemical composition similar to V4 C3 . These results suggested that the origin of the hydrogen trapping site with large trapping energy is not the misfit dislocation core but the carbon vacancy on the (001) broad surface of V4 C3 precipitates. Graphical abstract: Image 1